Performance Analysis of Active and Passive Fund Management: Evidence from the UK - Ahmed, Mohammad Sharfaraz (2020)
After the financial crisis of 2007-08 in the global financial market, the much-debated topic related to equity or share market has shifted its focus towards the performance analysis of active fund management and passive fund management. In the past papers, researchers have mentioned this topic of fund management as a never-ending debatable topic among the investors, the practitioners, and the researchers. To evaluate this debate in the context of the UK market, this paper seeks to evaluate empirically the factors that affect the returns of the funds in the UK and the superiority of one type of fund over the other one. In this research paper, we have evaluated the performances of 1,552 funds of both the passive fund management (Exchange Traded Funds) and the active fund management (Mutual Funds) based on different factors that affect the returns of the funds for the period of 5 years from 2015 to 2019. Based on the analysis in this research paper, the results indicate that the skills of the fund managers, the return from the equity market, and the return from the bond market are statistically significant and have positive impacts on the returns of the funds at a 5% significant level. This paper also exhibits that passive fund management is positively significant with the return of the funds than that of active fund management.